(untitled) (Saúde Ética & Justiça, 2012)
The present study has the objective analyze the medical, legal and ethical challenge imposed by the debate of use of organs from anencephalic neonates for transplantation from the point of view bioethics in Brazil. The path to achieve the goal was the method descriptive and exploratory; the literature search conducted from books, magazines, papers, journals. Anencephaly, is a severe defect of the embryonic central nervous system, has been the subject of heated debates in several sectors of Brazilian society and several questions can be brought up: i. Babies with anencephaly may be considered as persons? ii. Are they potential organ donors? iii. If so, under which circunstances? iv. Can the definition of death or brain death be changed? v. Is it should be practice intensive support of life for neonates with anencephaly? vi. How the priorities should be determined in neonatal units with limited resources? The present project has as main goal contribute to the debate about the anencephalic as organ donor, the legal and ethical issues surrounding the topic.